Odpowiedzi

Najlepsza Odpowiedź!
2010-02-24T10:42:58+01:00
X+2y=1
-3x+y=-5

x=1-2y
-3*(1-2y)=-5

x=1-2y
-3+6y=-5

x=1-2y
6y=-5+3

x=1-2y
6y=-2/6

x=1-2y
y=-1/3

x=1-2*(-1/3)
y=-1/3

x=1-(-2/3)
y=-1/3

x=1i 2/3
y=-1/3
2010-02-24T10:43:23+01:00
Metoda przeciwnych współczynników

x+2y=1 / *3
-3x+y=-5

3x+6y = 3
-3x+y = -5 dodajemy stronami i x się zerują

7y = -2 / :7
y = - ²/₇ -> podstawiamy do pierwszego równania

x+2y=1
x+ 2 * (- ²/₇ ) = 1
x - ⁴/₇ = 1
x = 1 + ⁴/₇
x = 1⁴/₇

x= 1⁴/₇
y= - ²/₇
2010-02-24T11:28:19+01:00
X+2y=1
-3x+y=-5

x=1-2y
-3(1-2y)+y=-5
-3+6y+y=-5
7y=-2
y=-2/7

x=1-2*(-2/7)
x=1+4/7
x=1⁴/₇